Analysis of a Composite High-Rise Building Frame Under Lateral Forces Considering Tuned Liquid Dampers using ETAB - Soni, Suneel Kumar; Patel, Rakesh; Chand, Naveen (International Journal of Scientific Research in Civil Engineering, 2019)
Current trends in construction industry demands taller and lighter Steel structures, which are flexible and having quite low damping value. This increases failure possibilities and also, problems from serviceability point of view. Several techniques are available today to minimize the vibration of the structure, out of which TLD is a new concept. The main motive of this study is to determine the effectiveness of structure considering TLD (Tuned liquid damper technique) for controlling vibrations generated over a structure due to lateral forces. In this study we will analyze a tall structure considering seismic zone III & V as per Indian provision, and compare a general conventional structure with TLD assigned structure to prepare a comparative study using Analysis tool ETABS. Designing of the tall structure is done as per IS-800 : 2007 (General code for Design of Steel Structure).